(untitled) - Shiza Saleem Ullah, Ghada Al Hothali (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Today the field of advertising is going through fundamental changes. The digitalization has resulted in new types of media such as the mobile phone, which offers richer possibilities to reach consumers and interact with them. Public attitudes toward advertising have been a focus of attention for a long time. Earlier researchers found that consumers have a positive attitude towards general advertising but a few later researchers found that consumers have a negative attitude towards mobile advertising. Therefore, this study identifies the consumer attitudes towards mobile advertising in the Kingdom of Saudi Arabia. The study conducted has relied on two main sources, namely secondary sources and questionnaire. The secondary sources helped get a better insight of the consumer attitudes towards SMS advertising in general. The questionnaire helped to get a better understanding of the market that exists mainly in Jeddah, how consumers perceive SMS advertising in context of entertainment, informativeness, irritation & credibility and what are the antecedents that exist for purchase intentions. Based on the obtained result, majority of the Saudi consumers considered SMS advertising to be informative and credible but are not willing to receive SMS advertising in the future.